The SERP Approach to Problem-Solving Research, Development, and Implementation. Issue 14 (December 2013) - Donovan, M. Suzanne; Snow, Catherine; Daro, Phil
Education researchers are increasingly working in practice-based partnerships in order to direct their research efforts toward important problems of practice. We argue for the creation of an infrastructure to support routine and sustained interaction among researchers, practitioners, and designers in order to make partnership efforts more efficient and effective over time. We describe SERP's efforts to initiate such an infrastructure through the creation and operation of "field sites"—long-term research, development, and implementation partnerships with school districts. We describe principles for field site operation and for product design that are emerging through our "learning by doing" approach. And we argue that the field site partnerships have produced work that is fundamentally different in character and content because of the SERP rules of engagement. SERP work is also more coherent because of its interdisciplinary character, and the sophistication of the partnership's work grows over time as related lines of work become integrated and as those engaged in sustained collaboration learn from each other.